Prevalence of the Skipping Breakfast among the Iranian Students: A Review Article - Mahin GHAFARI; Amin DOOSTI-IRANI; Masoud AMIRI; Zahra CHERAGHI (Tehran University of Medical Sciences, 2017)
Background: Adolescence is an important period since the establishment of dietary pattern can also affect the adulthood. This study aimed to estimate the overall prevalence of skipping breakfast among Iranian students. Methods: The international and national databases, including Medline, Scopus, Science Direct, Embase, Web of sciences, Google Scholar, MagIran, and SID were searched 1945-2016 as per case. All studies addressing the prevalence of skipping breakfast among Iranian students were extracted. Results: Out of 322 records, 24 articles remained for meta-analysis. The total pooled prevalence of skipping the breakfast was 0.216 (95% CI: 0.213-0.22), the girls had a higher percentage for skipping breakfast compared with boys (26% vs. 18%). Conclusion: Skipping breakfast is more prevalent in girls. Interventions are required to promote breakfast consumption in the targeted Iranian students, especially the girls.